O conceito de resiliência em um cenário diante da pandemia de COVID-19: uma perspectiva psicanalítica - Godinho, Marluce Trindade da Costa (Universidade Federal do Tocantins, 2023)
The human experiences throughout his life several challenges and situations that affect his psychic state and mental health and thus, it is important to know mechanisms to overcome these adversities, and the practice of resilience and its benefits are fundamental in the construction of psychic well-being. . The present research aims to explore the concept of resilience in a COVID19 pandemic scenario, approaching from the theory of drives built by Freud and explored by other thinkers. After the catastrophe that occurred in 2020, which claimed the lives of approximately six million people around the world, it was necessary to seek mechanisms to preserve the mental health of those who stayed and who suffered from the loss of their loved ones, financial losses and constant uncertainty about the future control over their own lives. In this sense, the objective of this work is to discuss the main changes arising from the global crisis caused by the coronavirus and to relate through Freudian theory what resilience and the ability to face adversity would be with possible defense mechanisms and the formation of the gallbladder addressed by Freud in text Beyond the Pleasure Principle (1920).